Medical Abortion of a First-Trimester Pregnancy with Large Multiple Uterine Leiomyomata - Somsook Santibenchakul; Unnop Jaisamrarn (Hindawi Limited, 2021)
Introduction. Termination of pregnancy in a patient with huge uterine leiomyomata poses significant challenges to clinicians. In this study, we report the successful termination of pregnancy in a patient with large multiple uterine leiomyomata using a combined regimen of drugs for medical abortion. Case. A 42-year-old woman, 6 weeks pregnant, presented to the Family Planning Clinic with an unintended pregnancy. She had a large, irregular abdominal midline mass, equivalent in size to 30-32 weeks of pregnancy. Abdominal and transvaginal ultrasound examinations revealed a small intrauterine gestational sac with a yolk sac and multiple large uterine leiomyomata. Treatment with mifepristone (200 mg) was initiated at the clinic. In addition, she was instructed to sublingually take 800 μg of misoprostol after 24-48 h. Two weeks later, at the follow-up visit, the patient complained of continued light bleeding. A pelvic examination showed that her cervix was dilated by 1 cm. In addition, abdominal and transvaginal ultrasound revealed a thick, inhomogeneous endometrium. Owing to light bleeding and no anemia or infection, the patient received two additional doses of 800 μg misoprostol vaginally. Her bleeding subsided for 61 days, and she resumed her normal menstrual cycle. Conclusion. A first-trimester pregnancy with large multiple uterine leiomyomata can be safely terminated using a combination regimen of drugs for medical abortion. However, an additional dose of misoprostol is required for the successful termination of pregnancy.